Novel Synthesis and Promising Applications of Graphene Nanostructures - Ijeomah, Geoffrey; Fahmi, Samsuri; Mohamad Adzhar, Md Zawawi (Penerbit Universiti Malaysia Pahang, 2017)
The transition from semi-metallic to semiconducting states in graphene has ushered in nanostructured materials with novel and enhanced electrical, mechanical, physiochemical and optical properties. The scope of graphene and its potential for novel applications could be substantially impacted by this transition. This article reviews the properties, recent synthesis methodologies and emerging applications of this wonder nanomaterial. The differentiations among the merits and challenges of current techniques are made, aiming to offer evidences to develop scalable and novel synthesis methodologies. The emphasis is on the synthesis, and the possible emerging promising applications arising from these conversion methods, and their overwhelming implications on our current knowledge of graphene and graphene nanostructures.